Maternal hemodynamics early in labor: a possible link with obstetric risk?. (10th April 2018) - Valensise, H.; Tiralongo, G. M.; Pisani, I.; Farsetti, D.; Lo Presti, D.; Gagliardi, G.; Basile, M. R.; Novelli, G. P.; Vasapollo, B.
Abstract: Objective: To determine if hemodynamic assessment in 'low‐risk' pregnant women at term with an appropriate‐for‐gestational age (AGA) fetus can improve the identification of patients who will suffer maternal or fetal/neonatal complications during labor. Methods: This was a prospective observational study of 77 women with low‐risk term pregnancy and AGA fetus, in the early stages of labor. Hemodynamic indices were obtained using the UltraSonic Cardiac Output Monitor (USCOM ® ) system. Patients were followed until the end of labor to identify fetal/neonatal and maternal outcomes, and those which developed complications of labor were compared with those delivering without complications. Results: Eleven (14.3%) patients had a complication during labor: in seven there was fetal distress and in four there were maternal complications (postpartum hemorrhage and/or uterine atony). Patients who developed complications during labor had lower cardiac output (5.6 ± 1.0 vs 6.7 ± 1.3 L/min, P  = 0.01) and cardiac index (3.1 ± 0.6 vs 3.5 ± 0.7 L/min/m 2, P  = 0.04), and higher total vascular resistance (1195.3 ± 205.3 vs 1017.8 ± 225.6 dynes × s/cm 5, P  = 0.017) early in labor, compared with those who did not develop complications. Receiver–operating characteristics curve analysis to determine cut‐offs showed cardiac output ≤ 5.8 L/min (sensitivity, 81.8%; specificity, 69.7%), cardiac index ≤ 2.9 L/min/m 2 (sensitivity, 63.6%; specificity, 76.9%) and total vascular resistance > 1069 dynes × s/cm 5 (sensitivity, 81.8%; specificity, 63.6%) to best predict maternal or fetal/neonatal complications. Conclusions: The study of maternal cardiovascular adaptation at the end of pregnancy could help to identify low‐risk patients who may develop complications during labor. In particular, low cardiac output and high total vascular resistance are apparently associated with higher risk of fetal distress or maternal complications. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.